2015
DOI: 10.2166/wst.2015.035
|View full text |Cite
|
Sign up to set email alerts
|

Microbial fuel cell-based biosensors for environmental monitoring: a review

Abstract: The microbial fuel cell (MFC) is an innovative technology that was initially designed to harness energy from organic waste using microorganisms. It is striking how many promising applications beyond energy production have been explored in recent decades. In particular, MFC-based biosensors are considered to be the next generation biosensing technology for environmental monitoring. This review describes recent advances in this emerging technology of MFC-based biosensors, with a special emphasis on monitoring of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 43 publications
0
70
0
2
Order By: Relevance
“…Microbial fuel cells (MFCs) are renewable energy technology transducers [4], which has the potential for application in wastewater treatment plants [5,6], electrical devices [7,8], and biosensor [9,10], because it can use bacteria for generating electricity from waste water. However, the power densities of MFCs are still low due to their high internal resistances [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Microbial fuel cells (MFCs) are renewable energy technology transducers [4], which has the potential for application in wastewater treatment plants [5,6], electrical devices [7,8], and biosensor [9,10], because it can use bacteria for generating electricity from waste water. However, the power densities of MFCs are still low due to their high internal resistances [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, properly combining energy generation and sensing functionalities from MFCs, self-powered devices, i.e., operated without any external electricity supply, can be designed to operate autonomously for remote detection and quantification of desired parameters [109,110]. Indeed, several reviews have already been reported regarding those unique and novel applications posed for MFCs as electrical biosensors [54,111].…”
Section: Mfc As a Self-powered Biosensor Versus A Traditional Whole-cmentioning
confidence: 99%
“…Since the analytical output signal is already measured as an electric current, MFC-based biosensors do not need an external transducer. Therefore, MFC-based biosensors are considered to be recyclable and sustainable devices with higher cost-and energy-efficiency than conventional biosensors [111].…”
Section: Mfc As a Self-powered Biosensor Versus A Traditional Whole-cmentioning
confidence: 99%
“…For a detailed summary of conductive mineral (e.g. metal oxides) enabled high-performance bioelectrochemical devices, the audience may refer to several recently published reviews on the fundamentals and applications of bioelectrochemical systems (Ge et al 2014;Lovley and Nevin 2013;Sun et al 2015;Wang and Ren 2013;Yong et al 2015).…”
Section: Bioelectrochemical Applicationsmentioning
confidence: 99%